Integrating molecular basis of sustainability to teaching learning sequence of fireretardant bamboo as sustainable material: Results from qualitative content analysis - Aulia, Afifah; Hernani; Mudzakir, A (AIP conference proceedings, 2022)
Students always feel about self-awareness on their cognitive functions as a part of metacognitive beliefs. This aspect is being important to support learning process consistently. The aim of this case study was assessed students' metacognitive beliefs during learning science. The Metacognition Questionnaire-30 (MCQ-30) which is being instrument for this study, consists of five subscales namely positive beliefs about worry, negative beliefs about uncontrollability and danger of worry, cognitive confidence, need to control thoughts, and cognitive self-consciousness has been developed originally by Wells and Cartwright-Hatton (2004). The questionnaire (30 items) which rated on a 4-point Likert scale was administered to l02 students from science education study program at public university in Bandung, Indonesia. This research subject come outs from all students in one study program for all batches. Rasch Model shows that Person Reliability is 0.7l and Item Reliability is 0.98, therefore the MCQ-30 fitted to use for university students. Results describes that the highest response is students trust their memory while the lowest response is they are not punishing themselves if they are not control their thoughts. Lastly, how to manage the students' memory during learning science is to be implication for further research.